Face Recognition LBP Feature Extraction and PCA Techniques (International Journal of Scientific Research and Management (IJSRM), 2017)
Face recognition is one of the security methods in biometric system in world wide area. Different mathematical calculations are used to perform face recognition. In this paper, Linear Binary pattern is applied to the different ORL face database. Linear discriminant analysis is applied followed by linear binary pattern. In this, different component analysis and training set data reduction is done by PCA techniques. The Feature extraction & pattern recognition is done by LBP method. The classification rate is achieved up to 94.7